Evaluation of Corrosion of Geothermal Power Generation Utilization of Reinforced Concrete Structure - Jin-A Jeong, Kyung Hwang Lee (Mathematical Statistician and Engineering Applications, 2023)
Geothermal power produces electricity as an energy source for the earth's internal heat. The temperature in the ground, close to the earth's surface, is kept at around 10~20?. With these characteristics, it is possible to build a heating and cooling system using a heat pump. The heat exchange with the ground is carried out through a heat exchanger, in which the refrigerant acts as a medium for heat transfer. Generally, the heat exchanger is completed by drilling a hole of 100 meters, inserting a U-shaped tube, and filling the space between the tube and the hole with grouting material. On the other hand, reinforced concrete has many advantages such as high strength expression, economy due to low cost, and long service life, so it is the most widely used construction material worldwide. Recently, due to the price increase of steel materials and the increase in logistics costs, the total construction cost has doubled. In this study, pipe rebar was developed to reduce steel materials, and since it is a pipe rebar that increases the strength of the material, there is no problem in terms of strength, but since corrosion resistance has not been reviewed, the corrosion resistance was evaluated in various corrosive environments to use pipe rebar as geothermal power generation. As a result of the experiment, it is judged that pipe rebar can be used as an alternative to the general rebar used in existing buildings. In addition, it is found that pipe rebar can be used as a geothermal heat exchanger piping.